Effects of Some Heavy Metals on Hatching of Fertilized Eggs in Four Marine Fish Species in Aliaga Bay (Eastern Aegean Sea), Turkey - BULUT, MUSA; AKBULUT, MEHMET; SUAT ATES, A.; MENDES, MEHMET (Asian Journal of Chemistry, 2010)
The present study was carried out to determine the effects of some heavy metals such as Cd, Mn, Zn on hatching success of fertilized eggs of four marine fish species, Dicentrarchus labrax (Linnaeus, 1758), Sparus aurata (Linnaeus, 1758), Dentex dentex (Linnaeus, 1758), Lithognathus mormyrus (Linnaeus, 1758) in Aliaga Bay (Eastern Aegean Sea). The relationships between heavy metal concentrations in eggs and their hatching success were determined by multiple linear regression analysis. Results showed that magnitude and type of the effects of the three heavy metals studied in this research on egg hatching ratios differed based on fish species. In terms of the magnitude of the effect, Zn has a greater effect than Cd and Mn on the hatching in D. dentex, while it is smaller in D. labrax. The effects of Zn on egg hatching are in the same direction and about the same level for S. aurata and L. mormyrus.